Tourists in Nepal: A Study of Travel Motivation and Consumer Behaviour in Selecting Destination - Devika S; Sreenath Muraleedharan K (Communications of International Proceedings, 2021)
Nepal is a land-locked country with rich cultural heritage. Numerous references can be pointed out from literature written from time immemorial about the beliefs, customs and spiritual significance of the country along with its unique blend of Hinduism and Buddhism. Various pilgrimages made by the travellers from India and China to Nepal, considering the country as abode of God, lead to the promotion of tourism in commercial aspects. The unification of Nepal in 1951 opened the doors to foreigners in great numbers to enter the country without facing the obstruction of red tapes to get a visiting visa. Nepal soon attained its growth as a tourist destination possessing untamed geography, counter-cultural environment and mystifying spirituality. This paper analyses the counter-cultural environment provided by Nepal to the tourists and its impact on tourism.
Keywords: Nepal; heritage; tourist destination; counter-culture.